Potential Reduction of Travel Times and Energy Consumption of Tilting Body Vehicles on ZSR - Grencik, Juraj; Klinko, Miloslav (Communications - Scientific letters of the University of Zilina, 2001)
Increasing the speed of passenger transport becomes an important task facing present-day railways. This task has risen both from the international agreements and from the necessity to keep competitiveness of the railway on the transport market. The paper presents a possibility to increase travel speed of passenger transport on ŽSR (Slovak Railways) by use of tilting body vehicles. For the selected ŽSR track sections accessible travel times were calculated for conventional design vehicles and for tilting body vehicles. From comparison of the results a remarkable reduction of accessible travel times can be found. Further, the energy-consumption demands have been evaluated for similar train sets of conventional design compared with the Pendolino train set during run on the existing track under present-day speed limits and under the theoretical speed limits from curve negotiation by tilting body vehicles.